The adoption of a flexible diet compared to the adoption of a restrictive diet: A literature review (Research, Society and Development, 2023)
The study observed changes in body image over time, especially among adolescents, influencing the pursuit of perfect bodies and leading to choices of restrictive diets. However, a more flexible approach proved beneficial, promoting healthy behaviors and outcomes while maintaining a positive relationship with food. Social pressure for a perfect body impacted mental health, disrupting individuals' relationships with food. The comparative research between restrictive and flexible diets highlighted the risks of rapid weight loss, and the reality of adolescents in relation to food, with a focus on body image distortions, underscored that restrictive diets are not ideal for overall health. The literature review encompassed national and international scientific articles from 1981 to 2023, utilizing diverse sources such as BIREME, SciELO, CAPES, Google Scholar, books, websites, and PubMed. Data collection occurred from March to November, using keywords such as "dietary restriction," "restrictive diet," "mindful eating," "food selectivity," and "fad diets." It was concluded that flexible diets contribute to health and well-being, whereas restrictive diets can lead to trauma and food-related fears. Extreme restrictions often result in negative emotions, hindering healthy weight loss and a positive relationship with food. The flexible approach, emphasizing balance, social aspects, and well-being, is considered more sustainable in the long term.